Managing leading edges during assembly of the Wendelstein 7-X divertor. (29th November 2018) - Endler, M; Fellinger, J; Hölbe, H; Sunn Pedersen, T; Bozhenkov, S; Geiger, J; Grahl, M
Abstract: Divertor target plates of magnetic confinement experiments are usually intersected by the magnetic field under a shallow angle. If steps are present in the target surface, the resulting leading edges will receive a strongly increased heat load as compared with the surrounding target surface. A very precise alignment of the target components is required to limit the height of leading edges in all magnetic configurations. In preparation of the initial divertor operation phase of the Wendelstein 7-X stellarator, we combined a model calculating the thermal load pattern on the targets for each magnetic configuration with a time-dependent model for heat transport within the targets, with a model for carbon sublimation and with measurements of step heights between target components to estimate the carbon sublimation rates to be expected. In a few locations of the as-built and as-installed divertor, these were found to be critically high, such that a limitation of plasma performance might have resulted. By re-aligning one type of target component according to the results of our modelling, the expected carbon sublimation rates were strongly reduced to uncritical levels.